Bargaining theory trade unions, & industorial strike activity - Ashenfelter, Orley; Johnson, George E. (American Economic Review, 1969)
The purpose of this paper is to examine certain received theories of the firm, trade union behavior, and bargaining in order to derive testable implications concerning the conditions under which labor disputes are more likely to occur. There are at least three reasons why an investigation of industrial strike activity seems fruitful. First, it might be argued that, because of their relatively frequent disruption of key sectors of the economy, work stoppages are the most important public policy issue raised by the existence of trade unions. It would therefore be useful to know whether, as Hicks thought, the majority of actual strikes are doubtless the result of faulty negotiation [18, p. 146] or whether they are an inevitable part of the functioning of an institutionalized market economy. Although it has long been known that the level of strike activity follows the business cycle [23] [20] [29], this leaves open the questions of the behavioral relations involved and their stability over time. Second, data on industrial disputes provide a potentially rich source of material for testing the implications of bargaining theories which purport to explain the outcome of labor-management negotiations.' Yet little work seems to have been done to date on the application of bargaining theoretic models to nonexperimeiltal data. A third reason for undertaking a study of this problem stems from the continuing interest in the effect of unions upon both the relative wage structure and the rate of change of aggregate money wages. Most union power is derived from the threat of the strike, and, accordingly, we agree with Charles Holt's recent suggestion that . the theory and analysis of industrial disputes may belp to clarify the role that unions play in the determination of wages [19, p. 50].